The Translation, Dissemination, and Evolution of Poetry from the High Tang Dynasty in France - Wu, Jiahui (Journal of Social Science and Humanities, 2024)
The 17th to 18th centuries marked the beginning of cultural exchange between China and the West, during which Jesuit missionaries played a significant role. They introduced the latest Western thoughts and scientific advancements to China while providing detailed descriptions of China in their letters sent back to Europe. Additionally, they translated many Chinese texts, with French Jesuits contributing the most influential works. Among these translations were various collections of Tang poetry translated into French. In the 19th century, the first collection of Tang poetry in French was published in France. Subsequently, an increasing number of French translators, sinologists, and Chinese scholars became involved in the translation of Tang poetry, enriching the variety of French translations. The translation and dissemination of Tang poetry in France have become an important aspect of Sino-French cultural exchange, garnering attention from numerous scholars. While there have been significant research contributions from scholars in both countries, much of the work has been conducted from a macro view, lacking micro-level studies focused on specific periods of Tang poetry, particularly regarding the poetry of the High Tang period. In light of this, this paper organizes and analyzes different versions of French translations of Tang poetry, primarily selecting works by prominent High Tang poets such as Li Bai, Du Fu, and Wang Wei. Through comparative analysis, the paper aims to explore how the translations reflect the French translators' understanding of High Tang poetry and the cultural concepts behind them.